The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/ajhb.22570
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐environmental variables associated with malnutrition and intestinal parasitoses in the child population of Misiones, Argentina

Abstract: The similarity between rural and middle urban groups in stunting prevalence reveals that cities are not healthier than rural environments. On the contrary, the fact that the rural group presents the lowest prevalence of overweight reaffirms that poverty and malnutrition are progressively moving from rural to urban areas, and that rural children have still more diverse and healthy diets favored by the consumption of homemade products (i.e., orchards, animal husbandry, etc.), placing them at an earlier stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 37 publications
2
12
0
16
Order By: Relevance
“…In this regard, studies in Venezuela and Paraguay reported a lower prevalence (63% and 35%, respectively) (19,20), but similar or slightly higher prevalence in studies performed in other Latin American countries. (21,22) In Argentina, prevalence was not uniform either since the distribution of parasitic infections changed according to region: values were over 80% in the north (16,23), between 60% and 70% in the center (24,25), and lower than 40% in the south (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, studies in Venezuela and Paraguay reported a lower prevalence (63% and 35%, respectively) (19,20), but similar or slightly higher prevalence in studies performed in other Latin American countries. (21,22) In Argentina, prevalence was not uniform either since the distribution of parasitic infections changed according to region: values were over 80% in the north (16,23), between 60% and 70% in the center (24,25), and lower than 40% in the south (8).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics provided information about indoor and outdoor housing conditions. Moreover, parents' educational level, employment, governmental food and monetary support, hygiene and cultural practices were considered, among others (15)(16)(17).…”
Section: Socio-environmental Studymentioning
confidence: 99%
“…Algunos autores han sugerido que las enteroparasitosis están relacionadas, por una parte, con factores geográficos y socioeconómicos, y por otra con el estado nutricional de los niños, debido a que conducen al retraso del crecimiento por inapetencia, competencia por los nutrientes, anemia por deficiencia de hierro, diarrea y síndrome de malabsorción, entre otros trastornos (4, 5). Los casos de poliparasitosis que causan infestaciones crónicas agravan aun más el cuadro clínico, especialmente en niños de edad escolar (6, 7).…”
unclassified
“…Previous reports in peri-urban areas from different Argentinean cities have shown that inadequate socioeconomic conditions adversely affect child growth (Cesani et al, 2010;Oyhenart et al, 2013). The prevalence of undernutrition and intestinal parasitoses was higher in peri-urban as compared with urban and rural areas Zonta, 2010;Zonta et al, 2014). These inadequate conditions affected both nutritional status and body composition (Marrod an Serrano et al, 2007).…”
mentioning
confidence: 99%